Peripartum cardiomyopathy: a review of prevalence and treatment trends from an African perspective - Kedir Negesso Tukeni; Kedir Negesso Tukeni; Elsah Tegene Asefa; Tamirat Godebo Woyimo; Esayas Kebede Gudina; Heidi Estner; Nikolaus Alexander Haas (Frontiers in Cardiovascular Medicine)
Peripartum cardiomyopathy (PPCM) is a type of dilated cardiomyopathy that develops in women without a history of heart disease during the last trimester of pregnancy or within 6 months postpartum. It is one of the primary causes of heart failure during pregnancy, which increases peripartum morbidity and mortality. PPCM can cause significant left ventricular dysfunction, progressive heart failure, and refractory cardiogenic shock, resulting in increased maternal morbidity and mortality. Dyspnea, exhaustion, and lower extremity edema are common symptoms and are often misdiagnosed as normal postpartum changes, demanding careful assessment with echocardiography. Furthermore, diagnosis and treatment are often delayed due to insufficient awareness among healthcare providers, with varying definitions of the disease across countries. Its underlying causes remain unclear, although recent studies point to a potential prolactin-oxidative stress mechanism that might lead to potential future treatments. Clinical care follows basic heart failure management guidelines while taking medication teratogenicity into account. The prognosis varies geographically based on the level and pattern of treatment, with a considerable number of patients displaying partial recovery. The prevalence and treatment patterns of these patients in Africa, including the benefits and safety profiles of bromocriptine, are reviewed here, to identify directions in its prospective use in different forms of cardiomyopathies based on the available literature.